WHAT STOPS YOU FROM STARTING YOUR OWN BUSINESS? A STUDY CONDUCTED ON STUDENTS OF THE ECONOMY AND BUSINESS FACULTY AT UNIVERSITAS TARUMANAGARA - Renli, Aeron; Wijaya, Andi (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to find the effect of perceived loss of financial resources, perceived loss of customer demand, and perceived loss of social support on fear of failure and negative emotion and the influence of fear of failure and negative emotion on entrepreneurial behavior tendency. This research uses non-probability sampling with purposive samples method to obtain 75 students of Faculty of Economics and Business in Universitas Tarumanagara as respondents in this research. The data is collected online through Google Forms. Data collected is processed with partial least square structural equation modeling (PLS-SEM) using SmartPLS 4 software. This research shows that perceived loss of financial resources is positively and significantly influenced both fear of failure and negative emotion, perceived loss of customer demand is positively and insignificantly influenced both fear of failure and negative emotion, perceived loss of social support positively and significantly influenced fear of failure, perceived loss of social support positively and insignificantly influenced negative emotion, fear of failure positively and significantly influenced negative emotion, and both fear of failure and negative emotion are positively and insignificantly influenced entrepreneurial behavior tendency.